Long-term effects of combined mindfulness intervention and app intervention compared to single interventions during the COVID-19 pandemic: a randomized controlled trial - Karing, Constance (Frontiers in Psychology, 2024)
Objectives The study examines the short-, middle-, and long-term effects of a combined intervention (face-to-face mindfulness intervention plus the mindfulness app 7Mind), compared to single interventions (face-to-face mindfulness intervention alone and an intervention via app 7Mind alone). The subgroups were compared with an active control group on mindfulness, mindful characteristics, mental health, emotion regulation, and attentional abilities during the COVID-19 pandemic. Additionally, the study explores whether students’ engagement with the app and their formal mindfulness practice at home improves intervention outcomes. Methods The study employs a randomized controlled trial approach involving three intervention groups and an active control group, with two follow-ups conducted over 12 months. The study included 177 university students who were randomly assigned to a mindfulness group (n = 42), a mindfulness app group (7Mind app, n = 44), a mindfulness + app group (n = 45), and an active control group (n = 46). The duration of the interventions was 4 weeks. The outcome variables were assessed at pre- and post-intervention, at 4 and 12 months post-intervention. Results At post-intervention and during both follow-ups, students in the combined mindfulness intervention did not demonstrate better outcomes compared to students in the single interventions or the active control group across all measures. Additionally, no statistically significant difference was observed between all interventions and the active control groups on any of the measures. However, it is noteworthy that all intervention groups and the active control group exhibited improvement in mindfulness, body awareness, emotion regulation, stress, and attentional abilities over the short, medium, and long term. Moreover, higher app usage in the app groups was significantly associated with increased body awareness. However, greater app use was also correlated with higher stress. Conclusion The results suggest that the mindfulness intervention and the mindfulness app were similar to the active control condition (communication training) on the investigated variables in the short, medium, and long term. Furthermore, an increased use of a mindfulness app can negatively affect stress.